Rebel governance: caliphate and democratic confederalism in the Syrian civil war (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2023)
The civil war in Syria, whichbroke out in 2011, saw the emergence of two alternative political projects facing the nation-state with revolutionary ideologies and aspirations for territorial control over large areas. On the one hand, the Caliphate project of the Islamic State in Iraq and Syria (ISIS); on the other, the Democratic Confederalism project of the Autonomous Administration of North and East Syria (AANES). This paper aims to analyse these alternative social orders, often defined as natural enemies, inside the framework of rebel governance, moving beyond the description of civil wars as a state of chaos and the exclusive state-centric discourse on governance. Initially, the concept of rebel governance is defined underlining its implications; secondly, the ideological foundations, the administrative, economic, and legal structures of the projects are discussed. The last section focuses on their similarities, differences and their power-ideology trade off in the context of their regional and international relations.
Keywords: Civil war; Syria; rebel governance; ISIS; AANES; Rojava